(3GdYbO GdKejf aj JGQjN GdHdO GdCejfs - (3Jbi GdOjf eMeO Hf eMeO Hf CMeO Hf Ydj GdMSfj GdaGSi Gdecj,J (B832 (3g` s ((3CHh HcQ Hf eMeO Hf eSYhO Hf PhGO GdYRGHi GdjGaYi GdTGaYi s)
(3ChdgG (B:s
(3MQa GdZjf (B( (3ZGdH Hf YjSi Hf CHj jhSa GdCfUGQi , CHh GdJeGe GdCfOdSi s
(3BNQgG (B:s
(3BNQg HYO PcQ ef de jYQa CSegG ef GdfSGA (B" (3Je GdLRA GdQGHY hHJeGeg Je LejY cJGH GdYbO GdKejf s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf hCSeGA GdeJQLejf HGdMeQIs
(3hai UOQ GdfSNI JedcGJ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs